Development and Application of Structural Health Monitoring System Based on Piezoelectric Sensors - Shi Yan; Jianxin Wu; Wei Sun; Haoyan Ma; Han Yan (International Journal of Distributed Sensor Networks)
Structural health monitoring (SHM) can enhance the functionality of structures, improve its safety and reliability, reduce maintenance costs, and increase the service life. A new kind of SHM technology based on piezoelectric ceramic transducers is an effective way to realize the prospective functions. However, many of piezoelectric ceramic SHM systems, which are complicated, weighty, and having much equipment, are mainly used for laboratory researches. In order to meet the needs of engineering applications, a portable piezoelectric concrete SHM system which uses the virtual instrument technology is proposed and produced in this paper. The developed system which is based on piezoelectric transducers can be realized to monitor online vibration accelerations, dynamic stresses, concrete cracks, and so forth. The function of this integrated system has been effectively proved in test and in an engineering application. The experimental and applied results show that the system is reliable, of high degree of automation, and portable. The work provides important technical support for improvement of structure design and monitoring of structural health status.